2022
DOI: 10.3389/fbioe.2022.849631
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcium Source on Pb and Cu Remediation Using Enzyme-Induced Carbonate Precipitation

Abstract: Heavy metal contamination not only causes threat to human health but also raises sustainable development concerns. The use of traditional methods to remediate heavy metal contamination is however time-consuming, and the remediation efficiency may not meet the requirements as expected. The present study conducted a series of test tube experiments to investigate the effect of calcium source on the lead and copper removals. In addition to the test tube experiments, numerical simulations were performed using Visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…Given that K sp (Ca(OH) 2 ) being 5.5 × 10 –6 is greater than K sp (Pb(OH) 2 ) being 1.2 × 10 –15 , Ca(OH) 2 tends to transform to Pb(OH) 2 . However, Pb(OH) 2 is deemed soluble when exposed to alkaline environments ( Edwards et al, 1992 ; Baltpurvins et al, 1996 ; Vítková et al, 2009 ; and Wang et al, 2022 ). When Pb(OH) 2 is just formed following the aforesaid transformation, and it is also on the way to dissolve, thereby releasing the Pb ions into the solution.…”
Section: Discussionmentioning
confidence: 99%
“…Given that K sp (Ca(OH) 2 ) being 5.5 × 10 –6 is greater than K sp (Pb(OH) 2 ) being 1.2 × 10 –15 , Ca(OH) 2 tends to transform to Pb(OH) 2 . However, Pb(OH) 2 is deemed soluble when exposed to alkaline environments ( Edwards et al, 1992 ; Baltpurvins et al, 1996 ; Vítková et al, 2009 ; and Wang et al, 2022 ). When Pb(OH) 2 is just formed following the aforesaid transformation, and it is also on the way to dissolve, thereby releasing the Pb ions into the solution.…”
Section: Discussionmentioning
confidence: 99%
“…The two ends converge to give an aggressive control of land degradation. According to the finding of this work, biomineralization technology may be used to precipitate calcium carbonate through catalyzing urea hydrolysis using the ureolytic bacteria ( Hu et al., 2021b ; Xue et al., 2022 ; Wang et al., 2022a , c ). The precipitation of calcium carbonate not only impedes the dissolution of calcite by the dolomitization but also reduces rates of land degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, urease is generated during the process of microorganic metabolism and catalyzes the hydrolysis of nitrogen-containing compounds to NH + 4 via Eqs 1-3, which is conducive to the production of MAP (MgNH 4 PO 4 • 6H 2 O) (Eq. 4) (Yu et al, 2021;Wang et al, 2022b). A previous study reported that MAP could be precipitated by adding NaOH to adjust the pH of the system (Yao, 2006), while the generated alkaline MAP could seriously damage the soil and, thus, limit its potential as a compound fertilizer for agriculture (Leng and Soares, 2021).…”
Section: Introductionmentioning
confidence: 99%